The politics between power and digital capital in China's cyberspace: a case study of Chinese digital games - Liu, Juan (Frontiers in Communication, 2023)
Based on a case study of digital games, this paper explores the politics between power and digital capital ingrained in the rapidly expanding Chinese cyberspace. The results show that digital capital and power in cyberspace form a paradoxical relationship that produces four sorts of politics: alliance, semi-alliance, disjunction, and semi-disjunction. Chinese modernity, as well as China’s unique capital structure and governance system, have contributed to these politics. It is these politics that have given rise to a more decentralized regulatory system, brought freedom and autonomy to cyberspace, and maximized the Chinese government’s power. Then digital capitalists in cyberspace can weave digital technology quickly into various social practices and make full use of netizens’ creativity. Consequently, the politics between the Chinese government and digital capitalists in cyberspace not only triggered an unexpected social transformation but also opened up a different path for Chinese digital technology.